Diseño de un banco de pruebas para la verificación de la presión de ajuste y el diferencial de cierre de válvulas de alivio con accionamiento por resorte directo y pilotada de 3” de servicio en líquidos. (2022)
The purpose of this project is to design a test bench which facilitates the verification process of the adjustment pressure and closing differential for pressure relief valves of a 3" size, in addition to following the guidelines mentioned in the applicable regulations and to carry out a correct verification. This seeks to offer an adequate tool that contributes to reducing possible errors and accidents that occur when carrying out the verification process of these devices and thereby reduce accidents in companies due to the lack of verification of safety valves. First, a contextualization about the pressure relief devices and their operation was carried out, as well as a compilation of the standards applicable to the design. With this, an interpretation of the data found was made and the design parameters for the project were determined; With this, 3 possible solution alternatives were proposed and an evaluation of them through a prioritization matrix. Following this, the detailed design of the components that make up the machine continued. Finally, the installation, operation and maintenance manuals were made, along with a financial analysis.